ANALISIS KESESUAIAN LAHAN BUDIDAYA RUMPUT LAUT JENIS Kappaphycus alvarezii (Doty) Doty DI PERAIRAN KABUPATEN SUMBA TIMUR - Wilson L Tisera (Politeknik Pertanian Negeri Kupang, 2020)
At present farming of Kappaphycus alvarezii is one of the main sources of income for the communities and East Sumba Regency. One important aspect in the context of optimizing seaweed farming there is the determination of suitability of farming areas) based on oceanographic parameters. This study aimed to analyze the level of suitability of farming areas of Kappaphycus alvarezii farmed using off-bottom method in East Sumba Regency. The study sites ware determined by purposive sampling at the locations of Kaliuda, Kandora, Tanaraing, Matawai Atu, Wanga, Daharwali, Mondu and Walakiri. Primary data on the physical-chemical factors of the waters and the existing conditions of farmed were collected in situ in the field. Analyzed of suitability of farming sites using a matrix of suitability, weighting and suitability level according to Utojo et.al (2004). The results found that the conditions of oceanographic factors that affect the growth and development of Kappaphycus alvarezii were in the optimal range for temperature, salinity, and pH; and tolerated for currents, substrates, water transparancy, depth and nitrates. Temperatures range from 29.33 to 31.00?C; salinity ranges between 34.33-34.67?/oo; pH between 7.57-7.83; currents between 0.14-0.25 m/sec; depth between 1.17-2.67 m; water transparancy 100%; nitrates between 0.20-0.35 mg/L. Substrate between coral sand to muddy sand overgrown with seagrasses. The suitability level of Kappaphycus alvarezii farming sites in all sampling locations was Sufficient, this means that the sampling locations representing seaweed farming in East Sumba Regency have limiting oceanographic factors that can be tolerated. Key Words: Kappaphycus alvarezii, oseanography, suitability level, East Sumba